2016
DOI: 10.14814/phy2.12625
|View full text |Cite
|
Sign up to set email alerts
|

Combined pharmacological activation of AMPK and PPARδpotentiates the effects of exercise in trained mice

Abstract: The combined activation of the cellular energy sensor AMP‐activated protein kinase (AMPK) and the nuclear transcription factor peroxisome proliferator‐activated receptor delta (PPAR δ) has been demonstrated to improve endurance and muscle function by mimicking the effects of exercise training. However, their combined pharmacological activation with exercise training has not been explored. Balb/c mice were trained on a treadmill and administered both the AMPK activator AICAR and the PPAR δ agonist GW0742 for 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 65 publications
2
16
0
Order By: Relevance
“…However, the increased expression of AMPK in AICAR-treated WT and R6/2 mice negated a potential increase in the ratio of p-AMPK to AMPK in these groups (Figures 1 A,B). This is consistent with previous reports showing modest effects of AICAR on AMPK phosphorylation in muscle following chronic administration ( 55 , 56 ), a phenomenon likely caused by habituation. Of relevance, we did not observe an effect of genotype in either AMPK or p-AMPK protein content in muscle from WT and R6/2 animals following AICAR administration, indicating that HD mice responded to treatment similarly to WT animals.…”
Section: Resultssupporting
confidence: 93%
“…However, the increased expression of AMPK in AICAR-treated WT and R6/2 mice negated a potential increase in the ratio of p-AMPK to AMPK in these groups (Figures 1 A,B). This is consistent with previous reports showing modest effects of AICAR on AMPK phosphorylation in muscle following chronic administration ( 55 , 56 ), a phenomenon likely caused by habituation. Of relevance, we did not observe an effect of genotype in either AMPK or p-AMPK protein content in muscle from WT and R6/2 animals following AICAR administration, indicating that HD mice responded to treatment similarly to WT animals.…”
Section: Resultssupporting
confidence: 93%
“…Basal indirect calorimetry was performed according to Manio et al. (). Mice were placed individually in acrylic chambers from the 3rd day before the last training session.…”
Section: Methodsmentioning
confidence: 99%
“…Lipids were extracted from powdered muscle samples as described in Manio et al. () with some modifications. Approximately 30 mg samples were mixed thoroughly with 1 mL Folch reagent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, numerous studies have shown that PPAR β / δ overexpression or activation in muscle dramatically improves FA utilization as energy source, reduces hyperlipidemia, improves endurance, and decreases insulin secretion from β -cells [32, 3537]. …”
Section: Ppars and Mitochondrial Metabolism In The Livermentioning
confidence: 99%